Pembinaan English Club SMPS IT Tahfizh Al Ikram Pesantren Ikramul Qur’an Bengkalis - Rionaldi Rionaldi; Boni Saputra (P3M Politeknik Negeri Bengkalis, 2025)
Community service activities at Bengkalis State Polytechnic aim to improve thinking skills, English language skills, and other necessary skills. In discussions with partners, namely the coordinator of the English Club at SMPIT Tahfizh Al Ikram, two main problems were identified: a lack of regular academic development activities outside of school and a lack of mentors to improve students' interest and English language skills. Therefore, this community service program was developed for the children in the English Club. The activities were conducted in 8 meetings over 2 months using cooperative learning and storytelling methods. Every weekend, participants learned through videos, pictures, discussions, and exercises, and were given weekly assignments. The output of these activities was an increase in students' interest and English language skills, as well as the publication of the results of the activities.